Invited Lectures from the 13th International Congress on Mathematical Education - Kaiser, Gabriele; Forgasz, Helen; Graven, Mellony; Kuzniak, Alain; Simmt, Elaine; Xu, Binyan (ICME-13 Monographs, 2018)
X, 786 p. 160 illus.